A Computational Model for the Radiated Kinetic Molecular Postulate of Fluid-Originated Nanomaterial Liquid Flow in the Induced Magnetic Flux Regime. (9th June 2021) - Hussain, Azad; Rehman, Aysha; Nadeem, Sohail; Khan, M. Riaz; Issakhov, Alibek
Abstract : The performance of mass transfer rate, friction drag, and heat transfer rate is illustrated in the boundary layer flow region via induced magnetic flux. In this recent analysis, the Buongiorno model is introduced to inspect the induced magnetic flux and radiative and convective kinetic molecular theory of liquid-initiated nanoliquid flow near the stagnant point. The energy equation is modified by radiation efficacy using the application of the Rosseland approximation. Through similarity variables, the available formulated partial differential equations are promoted into the nondimensional structure. The variation of the induced magnetic field near the wall goes up, and very far away, it decays when the size of the radiation characteristic ascends. The velocity amplitude expands by enlargement in the amount of the magnetic parameter, mixed convection, thermophoresis parameter, and fluid characteristic. The nanoparticle concentration reduces if the reciprocal of the magnetic Prandtl number expands. The temperature spectrum declines by enhancing the amount of the magnetic parameter. Drag friction decreases by the increment in the values of radiation and thermophoresis parameters. Heat transport rate increases when there is an increase in the values of Brownian and magnetic parameters. Mass transfer rate increases when there is incline in the values of the magnetic Prandtl and fluid parameter.